The Role of Thromboinflammation in Delayed Cerebral Ischemia after Subarachnoid Hemorrhage - McBride, Devin W.; Blackburn, Spiros L.; Peeyush, Kumar T; Matsumura, Kanako; Zhang, John H. (Frontiers in Neurology, 2017)
Delayed cerebral ischemia is a major determinant of patient outcome following aneurysmal subarachnoid hemorrhage. Although the exact mechanisms leading to delayed cerebral ischemia are not fully known, inflammation, cerebral vasospasm, and microthrombi may all function together to mediate the onset of delayed cerebral ischemia. Indeed, inflammation is tightly linked with activation of coagulation and microthrombi formation. Thromboinflammation is the intersection at which inflammation and thrombosis regulate one another in a feedforward manner, potentiating the formation of thrombi and pro-inflammatory signaling. In this review, we will explore the role(s) of inflammation and microthrombi in SAH pathophysiology and delayed cerebral ischemia, and discuss the potential of targeting thromboinflammation to prevent delayed cerebral ischemia after subarachnoid hemorrhage.